Energy-efficient Hybrid Optical-Electronic Network-on-Chip for Future Many-core Processors - Fu, Weiwei; Chen, Tianzhou; Liu, Li (Elektronika ir Elektrotechnika, 2014)
The increasing number of cores in future chip multiprocessors places a heightened emphasis on the energy-efficiency of the on-chip communications infrastructure. Traditional packet-switched electronic network-on-chip (NoC) has low energy-efficiency in transmitting long-distance packets. By providing high-bandwidth, low-latency chip-wide communication, optical interconnects can be a promising candidate for future NoC architectures. However, laser source and optical-electronic modems in optical network-on-chip (ONoC) introduce considerably high static energy, which is mostly wasted if the traffic load is low. In this paper, we propose a novel energy-efficient Hybrid Optical-Electronic NoC named HEON, which consists of an electronic buffer-bypassed mesh subnetwork and some bus-based optical channels. The optical channels, which dispose long-distance traffic to improve performance, are managed through a novel priority token scheme, in which the optical components can be dynamically turned on and off to save energy according to the traffic load. Experiment results show that HEON can improve energy-efficiency by 47.4 % and 38.1 %, compared with the electronic NoC and a state-of-art bus-based ONoC respectively. DOI: http://dx.doi.org/10.5755/j01.eee.20.3.6682